P55 Bleeding risk in patients with idiopathic pulmonary fibrosis (IPF) on nintedanib and con-current anticoagulation or antiplatelet therapy. (12th November 2019) - Denneny, EK; Vekaria, G; Sahota, J; Beitverda, L; Warner, C; Garthwaite, H; Heightman, M; Booth, H; Porter, JC
Abstract : Introduction: Nintedanib, one of two approved antifibrotic treatments for patients with IPF, is a tyrosine-kinase inhibitor whose inhibition of vascular endothelial growth factor poses a theoretical bleeding risk. Bleeding events were reported in 10% of patients in clinical trials 1 despite excluding patients at risk of bleeding including those on con-current anticoagulation (AC) or antiplatelet (AP) therapy. Consequently, Nintedanib is relatively contraindicated for patients with IPF on AC/AP treatment. Methods: We performed a retrospective analysis to examine bleeding risk within a tertiary-care ILD centre in the UK. Patients make an informed choice of anti-fibrotic and Nintedanib is offered even if patients are on AC/AP. Bleeding events were defined as intracranial, lower or upper gastrointestinal (GI) or respiratory tract (haemoptysis/epistaxis). Due to widespread prophylactic use of aspirin in both groups this was excluded from the analysis. Results: Of 317 patients with IPF (median age 76 years, 83% male), 118 (37%) were on Nintendanib and 79 (25%) on Pirfenidone. The remaining patients (48%) were outside criteria for, or had not tolerated, antifibrotic therapy. There were no significant differences in baseline characteristics. In the Nintedanib group 21 (17.8%) patients were also on an AC/AP: Warfarin (n=6), DOACs (n=6), dalteparin (n=2) and clopidogrel (n=7). This compared to 11 (13.9%) patients in the Pirfenidone group: Warfarin (n=1), DOACs (n=5) and clopidogrel (n=5). Of the 21 patients on an AC/AP in the Nintedanib group 1 (4%) had a bleeding complication (lower GI bleed on a DOAC), compared to none in the Pirfenidone group. There were no deaths in either group. Conclusion: Our results from real-life data demonstrate that 17.8% of our patients with IPF are on AC/AP and the overall incident of bleeding events in those patients taking both Nintedanib and an AC/AP, is similar to that reported for Nintedanib alone 1 . Our results suggest that con-current AC/AP doesn't increase bleeding risk and shouldn't be a reason to withhold Nintedanib. Further larger observational studies are needed to explore this risk further. References: European Medicines Agency. Ofev (nintedanib): EU product summary. 2015. http://www.ema.europa.eu/docs/en_GB/document_library/EPAR_-_Product_Information/human/003821/WC500182474.pdf. Accessed 15th July 2019.